Mechanisms of modification of magnesium– manganese alloys - E. I. Marukovich; V. Yu. Stetsenko; A. V. Stetsenko (Литьë и металлургия, 2023)
It is shown that the main modifying phases cannot serve as centers of crystallization of α‑phase microcrystals during solidification of magnesium‑manganese alloys.The superheating modification of these alloys is an adsorption‑nanostructural process. It is shown that adsorbed hydrogen acts as a modifying element of the structure of castings of magnesium‑manganese alloys. The mechanism of their modification by overheating consists of a significant decrease in the concentration of adsorbed hydrogen due to the predominance of its desorption processes from elementary magnesium and manganese nanocrystals in liquid magnesiummanganese alloys. The mechanism of modification of the main modifying phases of these alloys consists of a significant decrease in the concentration of adsorbed hydrogen in the melts through a significant decrease in the concentration of dissolved hydrogen.